PENGARUH VARIABEL EKONOMI DAN KARAKTERISTIK IBU RUMAHTANGGA TERHADAP KONSUMSI DAGING SAPI, DAGING BROILER DAN TELUR AYAM RAS RUMAHTANGGA DI KOTA PADANG - Jum’atri Yusri (Indonesian Journal of Agricultural Economics, 2012)
The purpose of this study is determining the factors affecting the meat, broiler and eggconsumption in Padang, West Sumatera. The primary data was used: householdspending on meat, broiler and egg consumption, the prices and housewife’scharacteristic (the housewife’s educational level, the housewife’s level of nutritionknowledge and the housewife’s occupation whose worked or not worked. Theanalytical method was Seemingly Unrelated Regression (SUR) with Almost IdealDemand System (AIDS) as the model. The study results showed (1) Variablessignificant effect on meat expenditure are meat price and the housewife’s level ofeducation (2) Meat expenditure share is relatively higher in household whosehousewife’s undergraduate (3) Variables significant effect on broiler expenditure aremeat price, broiler price, egg price, income and the housewife’s level of education (4)Broiler expenditure share is relatively lower in household whose housewife’sundergraduate (5) Variables significant effect on egg expenditure are egg price andbroiler price (5) There are differences in the behavior of consumption of meat, broilerand egg among household because of housewives’ educational level and housewives’occupation status.Keyword: housewife, expenditure share, educational level, level of nutritionknowledge, SUR, AIDS